Characteristics of cardiopulmonary exercise capacity in adults with different degrees of obesity - Deng, Shukun; Mei, Shengrui; Zhou, Qunyan; Zhi, Wenjun; Wu, Wenjun; Cai, Junyan; Yuan, Peng (Frontiers in Physiology, 2025)
ObjectiveTo explore the characteristics of cardiopulmonary exercise capacity in adults with different degrees of obesity through cardiopulmonary exercise test (CPET).MethodsFrom September 2019 to January 2024, the data of patients undergoing CPET in the Rehabilitation Department of the Affiliated Wuxi People’s Hospital of Nanjing Medical University were analyzed retrospectively. A total of 231 cases were included. They were categorized into five groups based on their body mass index (BMI): the control group (18.5 ≤ BMI < 24 kg/m2, n = 28), the overweight group (24.0 ≤ BMI < 28 kg/m2, n = 48), the mild obesity group (28 ≤ BMI < 35 kg/m2, n = 75), the moderate obesity group (35.0 ≤ BMI < 40 kg/m2, n = 47), and the severe obesity group (BMI ≥ 40 kg/m2, n = 33). Collected informations on the age, gender, height, and weight of five groups of participants. The VO2 at anaerobic threshold (VO2AT), percentage of predicted VO2AT (VO2AT% Pred), peak oxygen consumption (VO2peak), percentage of predicted VO2peak (VO2peak% Pred), peak kilogram oxygen consumption (VO2peak/kg), maximum exercise power (WRmax), breathing reserve (BR), maximum heart rate (HRmax), percentage of predicted HRmax (HRmax% Pred), maximum O2 pulse (VO2/HRmax), percentage of predicted maximum O2 pulse (VO2/HRmax%Pred), maximum relative O2 pulse (VO2/HRmax/kg),heart rate response (HRr), forced vital capacity (FVC), ratio of forced expiratory volume to vital capacity in 1 s (FEV1/FVC), percentage of predicted forced vital capacity (FVC% Pred), percentage of predicted forced expiratory volume ratio of 1 s (FEV1% Pred), peak expiratory flow rate (PEF), maximum exercise ventilation (VEmax), maximum voluntary ventilation (MVV) and other indicators during the CPET were collected. Single factor analysis of variance was used to compare the mean of each index between groups. Spearman correlation analysis was used to analyze the correlation between BMI and various indicators.ResultsThere was no statistical significance in gender composition, age, height, and exercise habit of the five groups of participants (P > 0.05). The body mass and BMI of the five groups had significant differences (P < 0.001). In terms of cardiopulmonary exercise capacity, there were statistical differences among the five groups in the overall distribution of VO2AT (H = 37.370,P < 0.001), VO2AT/kg (H = 34.747, P < 0.001), VO2peak (H = 23.018,P< 0.001), VO2peak/kg (H = 66.606, P < 0.001) and WRmax%Pred (H = 45.136, P < 0.001). There was no significant difference among the five groups in the overall distribution of VO2AT%Pred, VO2peak%Pred and WRmax. There were statistical significant difference among the five groups in HRmax (F = 2.443, P = 0.048), HRmax%Pred (F = 6.920, P < 0.001), VO2/HRmax (F = 8.803, P < 0.001), VO2/HRmax%Pred (F = 11.354, P < 0.001), VO2/HRmax/kg (F = 18.688, P < 0.001) and BR (F = 6.147, P < 0.001) and HRr (F = 9.467, P < 0.001). There were no significant differences among the five groups in RERmax (F = 0.336, P > 0.05). In terms of static pulmonary function, there were significant differences among the five groups in FVC%Pred (F = 4.577, P = 0.001), FEV1%Pred (F = 3.681, P = 0.006) and FEV1/FVC (F = 3.344, P = 0.011). There was no differences among the five groups in MVV(P> 0.05), and there were significant differences among the five groups in VEmax (P = 0.005) In terms of correlation analysis, BMI was positively correlated with VO2AT,VO2peak, VEmax and VO2/HRmax, and negatively correlated with VO2AT/kg, VO2peak/kg,WRmax%Pred, HRmax%Pred, VO2/HRmax%Pred, VO2/HRmax/kg,BR and HRr. In terms of static pulmonary function, BMI was negatively correlated with FVC%Pred, FEV1%Pred.ConclusionWith the aggravation of obesity, the maximum exercise ability of adults decreases, VO2peak/kg and VO2/HRmax%Pred decreases, and the breathing reserve decreases.